2017
DOI: 10.5465/amj.2014.0862
|View full text |Cite
|
Sign up to set email alerts
|

The Face of the Firm: The Influence of CEOs on Corporate Reputation

Abstract: It is widely assumed that CEOs shape how people view firms, but the question of how these leaders influence corporate reputations has received little theoretical or empirical attention.This study addresses two core questions in this vein: to what degree do leaders really matter for firm reputation, and which leaders affect their firm's reputation? We develop theory explaining how and why leaders should enter into evaluations of the firms that they lead. More specifically, we propose that CEOs will affect corpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 85 publications
6
126
0
3
Order By: Relevance
“…In the capital market, the media plays a key intermediary role in information disclosure, pooling, and diffusion, which significantly reduces the cost of information collection and reflects its governance functions (Liu, McConnell, & Xu, ). Prior studies show that media reports not only ease the information asymmetry between firms and stakeholders (Aerts & Cormier, ) but also affect the reputation of executives (Love et al, ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the capital market, the media plays a key intermediary role in information disclosure, pooling, and diffusion, which significantly reduces the cost of information collection and reflects its governance functions (Liu, McConnell, & Xu, ). Prior studies show that media reports not only ease the information asymmetry between firms and stakeholders (Aerts & Cormier, ) but also affect the reputation of executives (Love et al, ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The affirmation that the media plays an important role in the capital market has been widely accepted (Dyck, Volchkova, & Zingales, ). Media coverage is considered to not only ease the information asymmetry between firms and stakeholders (Aerts & Cormier, ) but also affect the reputation of executives (Love, Lim, & Bednar, ). Existing studies corroborate that media attention helps constrain executives' abuses of authority (Dyck et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…given the tendency to believe that CEOs personify the values and norms of companies (Fisman et al, 2013;Veltrop et al, 2018), in general, it is suggested that a greater media presence is associated with closer identification with the company (Love et al, 2017). Likewise, it is also argued that CEO media exposure is positively related to a longer time horizon in decision making (Hirshleifer et al, 2012;Liu et al, 2016).…”
Section: Complementary and Robustness Resultsmentioning
confidence: 99%
“…Second, other proxies for CEO commitment or CEO power could be considered, for example, CEO duality, CEO ownership, or whether CEO is a member of the family who holds majority stakes of the firm. Finally, the measure of CEO media exposure could be further developed by incorporating a consideration of the tone of CEO appearances in the press (Love et al, ), as the media agenda theory indicates that negative news are not symmetrical to the positive or neutral news (Kölbel, Busch, & Jancso, ; Rozin & Royzman, ). In this way, it would be possible to analyse the influence of positive and negative press mentions of the CEO to isolate the influence of each category on CSR.…”
Section: Discussionmentioning
confidence: 99%
“…When prominent partners, both internal and external, decide to collaborate with or support an organization, their reputation can reflect on the focal organization (Houston, 2003;Yu & Lester, 2008;Zavyalova, Pfarrer, Reger, & Shapiro, 2012). For example, prestigious internal members such as Chief Executive Officers can influence how stakeholders perceive the organization as a whole (Love, Lim, & Bednar, 2017). Similarly, external partners can shape the organization's reputation, and the choice of partners can strongly influence how stakeholders perceive the quality of the focal organization (Benjamin & Podolny, 1999).…”
Section: Reputation Spillover Effectsmentioning
confidence: 99%